William J. Ghent papers - Ghent, William J. (William James), 1866-1942.; Godfrey, Edward Settle, 1843-1932.; Paulding, Holmes O. (Holmes Offley), 1853-1883.
Correspondence, memoranda, writings, reports, notes, book reviews, subject files, clippings, printed matter, and photographs relating to Ghent's writings on the West and the socialist movement in the U.S. Reflects his views on economic conditions in the U.S. and socialism. Includes biographical sketches appearing in the Dictionary of American Biography and articles and book reviews appearing in trade journals. Also includes diaries of Edward Settle Godfrey and Holmes O. Paulding, participants in the Battle of the Little Bighorn, Mont., 1876. Correspondents include J. Neilson Barry, Charles Francis Bates, Charles A. Beard, E.A. Brininstool, P.E. Byrne, Elizabeth Bacon Custer, Frederick Samuel Dellenbaugh, Stella Madeleine Drumm, Fred Dustin, Grant Foreman, Edward S. Godfrey, Mary J. Pocock Godfrey, W.A. Graham, LeRoy R. Hafen, Grace Raymond Hebard, J. Franklin Jameson, Charles Kelly, Dumas Malone, Gustavus Myers, William W. Neifert, Allan Nevins, Don Russell, Edwin L. Sabin, Frederick A. Sims, Upton Sinclair, John Spargo, Mark Sullivan, George W. Webb, Maurice Williams, and Longmans, Green and Co.
Author and journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barry, J. Neilson -- 1870-1961 -- Correspondence; Bates, Charles Francis, -- 1862- -- Correspondence; Beard, Charles A. -- 1874-1948 -- Correspondence; Brininstool, E. A. -- 1870-1957 -- Correspondence; Byrne, P. E. -- 1869- -- Correspondence; Custer, Elizabeth Bacon, -- 1842-1933 -- Correspondence; Dellenbaugh, Frederick Samuel, -- 1853-1935 -- Correspondence; Drumm, Stella Madeleine -- Correspondence; Dustin, Fred, -- 1866- -- Correspondence; Foreman, Grant, -- 1869-1953 -- Correspondence; Godfrey, Edward Settle, -- 1843-1932 -- Correspondence; Godfrey, Mary J. Pocock, -- -1883 -- Correspondence; Graham, W. A. -- 1875-1954 -- Correspondence; Hafen, LeRoy R. -- 1893-1985 -- Correspondence; Hebard, Grace Raymond, -- 1861-1936 -- Correspondence; Jameson, J. Franklin -- 1859-1937 -- Correspondence; Kelly, Charles, -- 1889-1971 -- Correspondence; Malone, Dumas, -- 1892-1986 -- Correspondence; Myers, Gustavus, -- 1872-1942 -- Correspondence; Neifert, William W. -- Correspondence; Nevins, Allan, -- 1890-1971 -- Correspondence; Russell, Don, -- 1899-1986 -- Correspondence; Sabin, Edwin L. -- 1870-1952 -- Correspondence; Sims, Frederick A. -- 1867-1947 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Spargo, John, -- 1876-1966 -- Correspondence; Sullivan, Mark, -- 1874-1952 -- Correspondence; Webb, George Washington, -- 1856-1938 -- Correspondence; William, Maurice, -- 1881-1973 -- Correspondence; Longmans, Green, and Co. -- Correspondence; Dictionary of American biography; Indians of North America -- Wars -- 1866-1895.; Little Bighorn, Battle of the, Mont., 1876.; Socialism; Socialism -- United States; West (U.S.) -- History; United States -- Economic conditions -- 1865-1918.; United States -- Economic conditions -- 1918-1945.; Authors; Journalists